A fala: um fio da teia conceitual saussuriana - Giembinsky, Mariane Silva e Lima (2025)
The present study aimed to understand the place that parole occupies in saussurean studies, both in its conceptual aspect and regarding the accusation of its exclusion. To conduct this investigation, we divided the thesis into five distinct sections.In the first section, we discuss the treatment given to parole within the framework of historical-comparative linguistics, the field in which the Swiss linguist Ferdinand de Saussure was trained, with the goal of demonstrating how diverged from contemporary studies of his time concerning parole, focusing on the Neogrammarian proposal developed in the late 19th century. In the second section, we examine research on parole in the Course in General Linguistics, authored by Saussure and published in 1916, three years after his death, by his colleagues Charles Bally and Albert Sechehaye. They compiled teacher’s notes along with those from students who attended his lectures at the University of Geneva between 1907 and 1911. This reading is fundamental, as the accusation that Saussure excluded parole from linguistic studies often arises from this work, which introduced innovative ideas regarding the ways of con-ceiving and investigating human languages. We start from well-known distinction between lan-gue, language, and parole, referenced in Chapter III of the Introduction – The Object of Linguistics – and then move through his distinction between the Linguistics of langue and the Linguistics of parole, discussions that frequently support the claim that excluded parole. Next, we examine other sections of the book to analyze how the issue of parole is interconnected with other elements that make up Saussure’s linguistic theory and how the conceptual network we propose in this study takes shape. In the third section, we focus on Saussure’s theoretical elaboration regarding parole within the framework of the General Linguistics Courses he taught, whose students’ notes consti-tute one of the main sources for the Course in General Linguistics. In this part of our study, we seek to understand how parole was chronologically presented in his lectures at the University of Geneva, allowing us to trace a movement that aligns much more with the construction of a theory of parole than with its exclusion. In the fourth section, we conduct a deeper reading considering the critical apparatus that emerged in response to the various critiques of the book. To this end, we analyze critical inventories of the Course in General Linguistics, focusing on the issue of parole. Since the criticism of Saussure’s exclusion of parole is mainly based on this work, critical edi-tions play a significant role in the discussion of saussurean studies. Finally, in the fifth and last section of this study, we discuss the effects of a reductionist reading of parole based on the Course in General Linguistics and, drawing from our analyses, propose an alternative approach to parole in Saussurean thought—one that considers it as a thread within a conceptual network. Ultimately, we rely on the various materials we analyzed to understand how parole operates within saussurean linguistics.